Aromacología y salud: usos terapéuticos del perfume y cultura material entre las mujeres nazaríes (siglos XIII-XV) - Alba Abdel-fatah Martínez (Arqueología y Territorio Medieval, 2026)
In Nasrid society of the 13th and 14th centuries, perfumes and aromatic substances not only played an important symbolic and cultural role but also had therapeutic and health-related purposes, especially in women’s lives. This study analyses the use of aromatic remedies in women’s body care, connecting these practices with evidence from material culture, such as the perfume containers in the Alhambra Museum.Based on the analysis of Ibn al-Khatib’s medical texts and archaeological finds, the therapeutic uses of perfumes are explored, as well as their relevance in domestic and sanitary spaces. This interdisciplinary approach combines Arabic sources, the history of medicine, archaeology and gender studies to shed light on the links between the use of perfume, health and care practices amongst women in Nasrid Granada.